Bahasa Inggris - Sokhiful Jannah, Siti; Indra (Airlangga Journal of Innovation Management, 2024)
The development of economic trends and literacy in consumers entered uncertainty. The halal economy trend and industry have also progressed rapidly along with the increasing number of halal consumers worldwide. The influence of this halal trend is evident from Generation Z's preference for halal-labeled cosmetics, indicating their awareness of the halal status of cosmetic products. Therefore, it is important to observe factors behind Generation Z's purchase intention towards halal-labeled cosmetics in Bogor. This research used questionnaires to collect the data and applied a purposive sampling technique in sample collection. This study involved 103 respondents. This research was conducted in two places and used the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with the help of Smart-PLS 3.0 software. The first step is to evaluate the measurement model (outside the model) and the structural model (inside the model). This research provides insights to the cosmetic industry regarding the importance of halal certification in attracting the purchasing interest of Generation Z. From this research indicates a person's interest in purchasing halal cosmetics was mostly influenced by societal norms, attitudes toward halal items, and their capacity for self-control These findings can guide cosmetic manufacturers and marketers to enhance their marketing strategies and communications, focusing on halal values.